MARKETING APPROACHES TO CUSTOMER EXPERIENCE MEASUREMENT AND EVALUATION - A. Serzhantov; M. Orlova (Вестник университета)
The article shows the variety of existing marketing methods to measure and evaluate the consumer experience. The necessity of creation of a comprehensive Customer Experience Management System on the basis of empirical data in order to create a platform for building long-term relationships with customers is proved.